Systematic manipulation of glutathione metabolism in Escherichia coli for improved glutathione production. Issue 1 (December 2016) - Zhang, Jing; Quan, Cong; Wang, Cheng; Wu, Hui; Li, Zhimin; Ye, Qin
Abstract Background l -glutathione (GSH) is a non-protein thiol compound with important biological properties and is widely used in pharmaceutical, food, cosmetic and health products. The cellular GSH is determined by the activity and characteristic of GSH-synthesizing enzymes, energy and precursor supply, and degradation of formed GSH. Results In this study, genes encoding enzymes related to the precursor amino acid degradation and glycogen formation as well as GSH degradation were systematically manipulated inEscherichia coli strains over-expressinggshF fromActinobacillus succinogenes . The manipulation included disrupting the precursor degradation pathways (tnaA andsdaA ), eliminatingl -glutathione degradation (ggt andpepT ), and manipulating the intracellular ATP level (disruption ofglgB ). However the constructed mutants showed lower levels of GshF expression. 2-D electrophoresis was performed to elucidate the reasons for this discrepancy, and the results indicated obvious changes in central metabolism and amino acid metabolism in the penta-mutant. Fed-batch culture of the penta-mutant ZJ12345 was performed where the GshF expression level was enhanced, and both the GSH production (19.10 mM) and the yield based on addedl -cysteine (0.76 mmol/mmol) were significantly increased. Conclusion By interrupting the degradation pathways ofl -cysteine, serine and GSH and blocking glycogen formation, the GSH production efficiency was significantly improved.